Gradient residual stress evolution and its influence on fatigue life under combined carburising heat treatment and ultrasonic surface rolling process - Wang, Gang; Hou, Xiaofan; Zhang, Yue; Peng, Zhenlong; Xu, Guangtao; Zhao, Minghao (Engineering fracture mechanics, 2024)
•Carburizing heat treatment (CHT) combined with ultrasonic surface rolling process (USRP) were introduced to improve the rotary-bending fatigue behavior.•Rotary-bending fatigue life and surface integrity were improved after combined treatment (CHT + USRP).•The mechanism of gradient compressive residual stress (CRS) evolution affecting fatigue was revealed.•Two stages of gradient CRS relaxation were identified by the Kodama model. This study combined carburising heat treatment (CHT) with the ultrasonic surface rolling process (USRP) to improve the rotary bending fatigue properties of 18CrNiMo7-6 alloy steel. Based on the experimentally obtained fatigue limit (σ-1), the evolution of gradient compressive residual stress (CRS) of CHT- and CHT + USRP-treated specimens was analysed below the fatigue limit stress level. Subsequently, the evolution mechanism of gradient CRS of the two reinforced specimens was discussed and analysed from the opposing effects of austenite transformation and dislocation density change on the evolution of CRS. The results demonstrated that the selective bending fatigue performance of the alloy was evidently improved after the introduction of CRS; however, the change in fatigue limit was not evident. The durability under other loads (such as cyclic tension/compression and torsion loads) needs further study. The gradient CRS evolution of CHT specimens was mainly caused by the large residual austenite transformation and small dislocation density change. Therefore, the volume expansion caused by residual austenite transformation gradually increased the gradient compression residual stress of CHT specimens with an increased number of cycles. Contrarily, the degree residual stress evolution of CHT + USRP specimens was more affected by the dislocation density, and the gradient compression residual stress gradually decreased with an increased number of cycles. Finally, the residual stress evolution rate of the two reinforced specimens was divided into two stages: fast and slow.